Caretaker's Knowledge, Attitudes, and Practices Regarding the Causes, Treatments, and Risks of Diarrhea Among Under-Five Children in North-Eastern Tanzania: A Cross-Sectional Study - Edwin Adrian Liheluka MSc; Theodora Bali PhD; Eric Lyimo MSc; Denise Dekker PhD; Nyasiro Sophia Gibore PhD (SAGE Publishing, 2024)
Background . Pediatric diarrhea remains a public health concern. This study explored caretaker's knowledge, attitudes, and practices regarding the causes, treatments, and risks of diarrhea among under-fives in Korogwe and Handeni districts, north-eastern Tanzania. Methods . We conducted a qualitative, cross-sectional study. Participants were selected through purposive sampling. Data were gathered through in-depth interviews and focus group discussions, and they were analyzed using thematic analysis. Results . Most participants had good knowledge about the risks of diarrhea among under-fives. However, most participants had poor knowledge of the causes and treatments of diarrhea. A significant proportion of participants had negative attitudes and poor practices about the treatment of diarrhea. A small percentage of participants possessed positive attitudes and appropriate practices for managing diarrhea. Conclusion . To bridge the knowledge gaps among caretakers and promote positive attitudes and behaviors about the management of diarrheal diseases, health authorities are urged to strengthen health education in the study communities.